Formulation of Mouthwash Honje Laka (Etlingera Hemisphaerica (Blume) R.M.Sm.) Flower Extract Against Streptococcus Mutans - Ira Rahmiyani; Aneu Nia Rolita Pasa; Saeful Amin; Anna Yuliana (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Dental and oral health is an important part of physical health that requires our attention. Streptococcus mutans (S. mutans) is known as a cariogenic microorganism because it breaks down sugar and forms tooth substances for energy production. One of the preventive measures against the occurrence of chemical dental plaque is the use of mouthwash. Therefore, a mouthwash formulation from natural ingredients was developed. The potential plant for natural mouthwash is the honje laka flower (Etlingera hemisphaerica (Blume) R.M.Sm.) which contains flavonoids, polyphenols, quinones, monoterpenoids, and sesquiterpenoids as antibacterial. This study aims to determine the potential of honje laka flower extract in inhibiting the growth of S. mutans and as an ingredient in mouthwash. The procedure of this research started from the extraction of honje laka flower using 96% ethanol solvent followed by phytochemical screening test and antimicrobial test with a well diffusion method. The concentration of honje laka flower extract used for MIC test were 5%, 10%, and 15%. Evaluation of honje laka extract mouthwash preparations were organoleptic test, pH test, centrifugation test, cycling test, and bacterial inhibition zone test. The results showed the ethanol extract of honje laka flowers has activity against S. mutans with a MIC at a concentration of 5% and inhibition zone at 9.22±0.115 mm, while the mouthwash formula at a concentration of 15% has an inhibitory zone at 9.35±0.02 mm. As a conclusion, ethanol extract from honje laka flower can be used as a mouthwash and can inhibit the activity of S. mutans.